Purification and biochemical characterization of a novel β-fructofuranosidase from Penicillium oxalicum with transfructosylating activity producing neokestose. Issue 8 (August 2015) - Xu, Qiangsheng; Zheng, Xiaoqun; Huang, Meiping; Wu, Min; Yan, Yusi; Pan, Jiamao; Yang, Qi; Duan, Cheng-Jie; Liu, Jun-Liang; Feng, Jia-Xun
Graphical abstract: Highlights: A novel β-fructofuranosidase from P. oxalicum was purified and characterized. The enzyme could efficiently convert sucrose into the prebiotic neokestose. The enzyme exhibited remarkable stability over a broad pH range. Abstract: Neokestose is a novel fructooligosaccharide (FOS) exhibiting greater prebiotic effects and chemical stability than commercial FOSs. In this study, a neokestose-producing β-fructofuranosidase was purified from Penicillium oxalicum GXU20. The enzyme is a glycoprotein with an approximate 111 kDa molecular weight, and it has an N-linked carbohydrate composition that accounts for approximately 38% of its total mass. Optimal enzymatic activity occurred at pH 5.5 and 60 °C. The enzyme remained stable over a wide pH range (2–9.5). Metal ions and chemical reagents had no significant effect on its enzymatic activity, with the exception of silver (Ag + ). The enzyme could hydrolyze fructosyl-(2-1)-linked carbohydrates. Using sucrose as a substrate, the K m and V max values for a transfer reaction were 163.9 ± 10.3 mmol/L and 800.1 ± 19.8 μmol/(min mg), respectively, whereas the K m, V max, and K i values for a hydrolysis reaction with substrate inhibition were 48.3 ± 1.7 mmol/L, 1631.3 ± 28.2 μmol/(min mg), and 162.6 ± 4.9 mmol/L, respectively. In the catalysis of 500 g/L sucrose, the maximum concentration of neokestose and total FOS were 94.2 g/L and 224.7 g/L, respectively. Finally, the gene encoding the β-fructofuranosidase was cloned, analyzed, and functionally expressed in Pichia pastoris .